The naked truth about HIV and risk taking in Swedish prisons: A qualitative study. - Sigrid J A Lindbom; Markus Larsson; Anette Agardh (PLoS ONE)
Background This qualitative study explores former prison inmates' perceptions and attitudes towards HIV risk inside Swedish prisons. Method In 2014, eight semi-structured interviews were conducted with former male prisoners to gain a deeper understanding of situations perceived to be associated with risk of HIV transmission. The material gathered from the interviews was analyzed by manifest and latent qualitative content analysis. Results The findings revealed that risky behavioral practices, such as sharing needles, unprotected sexual activity, and lack of openness about HIV status represented potential health threats with regard to the risk of HIV transmission. Conclusions Evidence from the study indicates that educational interventions regarding HIV and the transmission routes are required for HIV prevention in Swedish prisons.